Complete Protection Against Yersinia pestis in BALB/c Mouse Model Elicited by Immunization With Inhalable Formulations of rF1-V10 Fusion Protein via Aerosolized Intratracheal Inoculation - Zhang, Wei; Song, Xiaolin; Zhai, Lina; Guo, Jianshu; Zheng, Xinying; Zhang, Lili; Lv, Meng; Hu, Lingfei; Zhou, Dongsheng; Xiong, Xiaolu; Yang, Wenhui (Frontiers in Immunology, 2022)
Pneumonic plague, caused by Yersinia pestis, is a serious infectious disease with high mortality rates when not treated early with antibiotics. Currently, no FDA approved vaccine against plague is available for human use. The capsular antigen F1, the low-calcium-response V antigen (LcrV), and the recombinant fusion protein (rF1-LcrV) of Y. pestis are lead subunit vaccine candidates under intense investigation, however, the inability of recombinant antigens to provide complete protection against pneumonic plague in animal models remains a significant concern. In this study, we compared immunoprotection against pneumonic plague provided by rF1-V10, rV10, and rF1 vaccinations delivered via aerosolized intratracheal (i.t.) inoculation or subcutaneous (s.c.) injection. We further considered three vaccine formulations, i.e., conventional liquid, dry powder produced by spray freeze drying, or dry powder reconstituted in PBS. The main findings are: (i) rF1-V10 immunization with any formulation via i.t. or s.c. routes conferred 100% protection against Y. pestis i.t. infection; (ii) rF1 or rV10 immunization via i.t. route provided significantly stronger protection than that induced by rF1 or rV10 immunization via s.c. route; (iii) powder formulations of subunit vaccines induced immune responses and provided protection efficacy at levels equivalent to those elicited by unprocessed liquid formulations of vaccines. Our data indicate that immunization with powder formulation of rF1-V10 vaccines via i.t. route could be a promising vaccination strategy for providing protective immunity against pneumonic plague.